2013
DOI: 10.1210/en.2012-1980
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Programming of the Fetal Male Hippocampal Epigenome

Abstract: The late-gestation surge in fetal plasma cortisol is critical for maturation of fetal organ systems. As a result, synthetic glucocorticoids (sGCs) are administered to pregnant women at risk of delivering preterm. However, animal studies have shown that fetal exposure to sGC results in increased risk of behavioral, endocrine, and metabolic abnormalities in offspring. Here, we test the hypothesis that prenatal GC exposure resulting from the fetal cortisol surge or after sGC exposure results in promoter-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 57 publications
3
59
1
Order By: Relevance
“…Substantial evidence indicates the importance of epigenetic modifications including DNA methylation in glucocorticoid signaling (Crudo et al, 2013;Sharma et al, 2013;Petropoulos et al, 2014). It has been shown that glucocorticoids repress gene expression by interacting with DNA (cytosine-5)-methyltransferase 3b and methyl CpG binding protein 2 and increasing promoter methylation (Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial evidence indicates the importance of epigenetic modifications including DNA methylation in glucocorticoid signaling (Crudo et al, 2013;Sharma et al, 2013;Petropoulos et al, 2014). It has been shown that glucocorticoids repress gene expression by interacting with DNA (cytosine-5)-methyltransferase 3b and methyl CpG binding protein 2 and increasing promoter methylation (Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that glucocorticoids repress gene expression by interacting with DNA (cytosine-5)-methyltransferase 3b and methyl CpG binding protein 2 and increasing promoter methylation (Sharma et al, 2013). Furthermore glucocorticoid exposure is associated with both methylation and demethylation of promoter and enhancer regions, illustrating a potentially complex regulatory pathway (Crudo et al, 2013;Thomassin et al, 2001). Crudo et al (2012) demonstrated that the endogenous glucocorticoid surge alters the expression of methylation specific genes such as DNA (cytosine-5)-methyltransferase 3b and methyl-CpG-binding domain protein 2 and is instrumental in defining DNA methylation patterns in an organ-specific manner (Crudo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data show similar effects of fetal glucocorticoid overexposure in different species, including mice, rhesus macaques and humans, such as reduced hippocampal volume with a reduced number of pyramidal neurons and pronounced degeneration of neuronal perikarya and dendrites, resulting in a decreased number of synaptic contacts (34,35). Epigenetic changes caused by antenatal treatment with synthetic glucocorticoids that alter genome-wide transcription and modify GR DNA binding in the fetal hippocampus during late gestation have been recently shown in guinea pigs (36).…”
Section: Antenatal Treatment and Fetal Hpa Axis Functionmentioning
confidence: 82%
“…Pregnancy and early postnatal environment could cause epigenetic changes in specific genes in offspring, and these changes can be continued to several generations (Lillycrop et al, 2005;Szyf et al, 2008;Weaver et al, 2004). Some studies have demonstrated that prenatal high level of GC exposure can induce epigenetic alteration in male offspring (Crudo et al, 2013), and a possible target of GC programming is the fetal hippocampus. Reports demonstrated that prenatal high level of GC exposure could induce the epigenetic alteration of specific genes, including glucocorticoid receptor (GR) and mineralocorticoid receptor (MR), in fetal hippocampus (Crudo et al, 2012;McCabe et al, 2001).…”
Section: Tablementioning
confidence: 99%